Desain User Interface Sistem Informasi Digital Dalam Menigkatkan UMKM Desa Pertumbukan Kecamatan Wampu - Putra, Randi Rian; Kurniawan, Fahmi; Yanti Yusman; Aldi Alvin (Jurnal Mahajana Informasi, 2024)
Effective user interface design in digital information systems can play an important role in improving the performance of Micro, Small and Medium Enterprises (MSMEs) in Pertumbukan Village, Wampu District. This research aims to design a digital information system that is easy to use and intuitive for MSMEs in the village. By using a user-centered design approach, this information system is expected to help MSMEs manage their business more efficiently, including inventory management, sales and communication with customers. The research methods used include literature studies, user needs surveys, as well as prototyping and interface testing. The research results show that simple, clear and responsive interface design can increase user satisfaction and efficiency, as well as encourage the adoption of digital technology among village MSMEs. The implementation of this information system is expected to have a positive impact on local economic growth by empowering small businesses to be more competitive in the wider market.